Press coverage as a heuristic guide for social decision-making about sexual offenders - Harper, Craig A. (Psychology, crime & law, 2017)
We present two studies examining the role of the British press in promoting heuristic-based decision-making about sexual crime. In Study 1, 1014 press articles were used in order to examine the role of the availability heuristic. That is, we used the recent high-profile Jimmy Savile sexual offending scandal to investigate how this case impacted upon press reporting of sexual crime. We found a 295% increase in the frequency of sexual crime coverage after this case, in addition to a 22:1 over-representation of sexual crime prevalence. Linguistically, tabloid stories about sexual crime did not significantly differ in the 12 months following the Jimmy Savile scandal, though broadsheets were less negative in their coverage after the scandal broke. Tabloid headline descriptors of sexual offenders were also substantially more offensive than those used by broadsheets. In Study 2, tabloid readership was associated with more negative attitudes and preferences for harsher punishments for sexual offenders, which we propose may be attributable to the affect heuristic. We discuss our findings within the context of dual-process cognition, and argue that the national press promote heuristic-based thinking about the issue of sexual offending. Future research avenues, and potential implications for press engagement, are also identified.